MOLECULAR DETECTION OF Plasmodium spp. IN Anopheles AND ITS VECTOR POTENTIAL IN LOW-ENDEMIC AREAS IN INDONESIA (Proceedings of the International Conference on Public Health, 2022)
Indonesia has 31.1% of regencies/cities categorized as low-endemic areas. Theareas are expected to accelerate the malaria elimination status; meanwhile, it is crucial toreduce the vector density in the area. Vector data updates in malaria-endemic areas areessential in anticipating the transmission and an increase in malaria cases. The purpose ofthe study was to get information on new malaria vector updates in low-endemic malariaareas in Indonesia. The study was conducted from 2015-2018 in Jambi, Riau Islands, SpecialRegion of Yogyakarta, Central Kalimantan, North Kalimantan, and South Sulawesi.Mosquito and larva collection was performed in low-endemic areas of malaria. We used thenight landing collection, animal-baited trap, livestock bait, light trap, and resting morningcollection. The Plasmodium was identified from Anopheles samples using the polymerasechain reaction (PCR) with Plasmodium genus-specific primers. The results showed a newpotential vector in low-endemic malaria areas in Indonesia. They are An. vagus (Jambi,Central Kalimantan, South Sulawesi, and Yogyakarta), An. kochi (Jambi), An. dirus and An.barbirostris (Central Kalimantan), and An. subpictus (South Sulawesi). The discovery of thesuspected Anopheles species as malaria vectors suggests a potential transmission, andincreased cases may occur. Vector surveillance needs to be strengthened to reduce malariatransmission.
Keywords: Anopheles; PCR; Low-endemic malaria; Vector